Огшоры эстон идиот = Tavaline eesti idioot: кылбуръес / Ю. Роосто - Роосто Юрген (Инвожо, 2011)
Экземпляры: ФО-3/1,5/2,6/3,8/4,11/5,14/6 (20130515) / Инвентарный номер: 1 / Цена: 100.00 / Авт.знак: Р 72 / ББК: 84.4(Эст)